2013
DOI: 10.1088/0957-4484/24/37/375701
|View full text |Cite
|
Sign up to set email alerts
|

Atomic roughness enhanced friction on hydrogenated graphene

Abstract: Atomic friction on hydrogenated graphene is investigated using molecular dynamics simulations. Hydrogenation is found to increase friction significantly, and the atomic-level information provided by the simulations reveals that atomic roughness induced by hydrogenation is the primary cause of the friction enhancement. Other proposed mechanisms, specifically adhesion and rigidity, are excluded based on the simulation results and analyses performed using the Prandtl-Tomlinson model. In addition, it is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 35 publications
7
66
0
Order By: Relevance
“…However, this is not the sole criterion to observe superlubricity. The biggest challenge to realize superlubricity is perhaps establishing contact between two solid surfaces that are completely clean [10,25,26], given the fact that the absorption and/or contaminants can easily hinder superlubricity [25]. To the best of our knowledge, in all the experiments reported before 2012 for observing superlubricity, the two surfaces in contact were placed together.…”
Section: Challengesmentioning
confidence: 99%
“…However, this is not the sole criterion to observe superlubricity. The biggest challenge to realize superlubricity is perhaps establishing contact between two solid surfaces that are completely clean [10,25,26], given the fact that the absorption and/or contaminants can easily hinder superlubricity [25]. To the best of our knowledge, in all the experiments reported before 2012 for observing superlubricity, the two surfaces in contact were placed together.…”
Section: Challengesmentioning
confidence: 99%
“…These studies showed that the friction between graphene layers is significantly influenced by the normal load [16,21], commensurability [12-18, 22, 23], contact edge [21,[24][25][26][27], surface conditions [28][29][30][31][32][33], and environmental conditions such as humidity [34], etc. The friction force generally increases with increasing the normal load because it reduces the interfacial spacing and thus increases the interfacial shear resistance [16,21].…”
Section: Introductionmentioning
confidence: 99%
“…The edge barriers induced by the contact edge may enhance friction energy dissipation, which consequently results in an edge effect on the nanoscale friction -it depends not only on the contact area [18,21] but also on the contact edge [21,[24][25][26][27]. The surface conditions, such as defects [28,29], roughness [30] and morphology [31][32][33], may have strong effects on the interfacial interaction and thus have remarkable influence on the nanoscale friction. The interlayer friction coefficient of multilayer graphene decreases with the relative humidity of atmosphere, due to H and OH passivation of graphene [34].…”
Section: Introductionmentioning
confidence: 99%
“…Their results support the hypothesis and explain the decreasing friction by the ability of multilayers to act as single material and resist wrinkling [36]. Dong et al have analyzed the results of atomistic simulations of friction on hydrogenated graphene [37]. They concluded that the effects of hydrogenation on friction are mostly due to the enhanced atomic-scale roughness, excluding other suggested mechanisms such as changes in flexural rigidity or in adhesion [38].…”
Section: Atomistic Simulations Of Graphene Tribologymentioning
confidence: 70%